Critical metals handbook - Gunn, Gus, 1951- (Hoboken, New Jersey ; Chichester, West Sussex, UK : John Wiley & Sons : American Geophysical Union, 2014)
"The proposed book will provide a unique, one-stop source of information on diverse aspects of the critical metals, including geology, deposits, processing, applications, environmental issues and markets"--Provided by publisher.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Metals -- Handbooks, manuals, etc; TECHNOLOGY & ENGINEERING -- Metallurgy; Metals; Electronic books; Handbooks and manuals